ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA OPERASI HITUNG PECAHAN PADA SISWA KELAS V SDN PENGAWU - Indah Suciati; Dewi Sri Wahyuni (Universitas Sultan Ageng Tirtayasa, 2018)
This research aims to describe and analyze students' errors in solving the problem on the matter of fractional counting operations. The type of research used is descriptive explorative research with mixed methods. The population of this research is the students of grade V SDN Pengawu with the number of research subjects of 35 students. The results obtained that the concept error on fractional counting operations amounted to 53.86%, principal errors of 41.22%, and error calculation of 4.92%. For fractional addition operations, concept errors of 80.70%, principal errors of 13.16%, and calculation errors of 6.15%. For reduction operations, concept errors of 44.53%, principal errors of 49.92%, and calculation errors of 6.25%. For multiplication operations, concept errors are 50.00%, principal errors of 45.59%, and calculation errors of 4.42%. For fractional division operations, concept errors of 40.17%, principal errors of 57.26%, and calculation errors of 2.57%. Keywords: analysis of errors, concepts, principles, calculations, fractional counting operations.